Phytochemical analysis and cytotoxic activities of two distinct cultivars of Ganyong rhizomes (Canna indica) against the WiDr colon cancer cell line - IFANDARI; SITARINA WIDYARINI; L. HARTANTO NUGROHO; Rarastoeti Pratiwi (Society for Indonesian Biodiversity, 2020)
Abstract. Ifandari, Widyarini S, Nugroho LH, Pratiwi R. 2020. Phytochemical analysis and cytotoxic activities of two distinct cultivars of Ganyong rhizomes (Canna indica) against the WiDr colon cancer cell line. Biodiversitas 21: 1660-1669. Canna indica L is an edible plant with high nutrient content and positive health benefits. In Indonesia, edible canna is divided into two cultivar groups: red edible canna and green edible canna. Canna indica L. is investigated in this study as a potential medicinal plant for colon cancer in WiDr cell lines. The phytochemical contents of two distinct cultivars of edible canna (known in Indonesia as ganyong), namely red edible canna and green edible canna. These two discrete samples were extracted by using two different solvents, dichloromethane and ethanol, followed by evaluation using Fourier-transform infrared (FTIR) spectroscopy in order to detected functional group. In the analysis of the composition of the elements of chemical compounds, the samples subsequently injected into the liquid chromatography?high-resolution mass spectrometry (LC-HRMS). The cell viability assay was performed to evaluate the cytotoxic activities of extracted compounds from two cultivars of edible canna in two different solvents. FTIR results demonstrated that the red and green edible canna extracts contained 17 and 18 functional group compounds, respectively. Furthermore, the cell viability was lower in WiDr cells treated with dichloromethane extract of red than green edible canna or the ethanol extract of red edible canna. Notably, LC-HRMS results of the most potent dichloromethane extract of red edible canna revealed the presence of fatty acid compounds. These findings indicate that the two cultivars of edible canna could potentially be utilized as promising candidates for colon cancer treatment.